LIGHT EFFECTS ON IN VITRO ROOTING OF PEAR CULTIVARS OF DIFFERENT RHIZOGENIC ABILITY. - BERTAZZA, GIANPAOLO; RITA BARALDI , STEFANO PREDIERI
The effect of varying light regimes on in vitro rooting of microcuttings of two pear (Pyrus communis L.) cultivars was investigated. Cultures of the easy-to-root `Conference` and the difficult-to-root `Doyenne d`Hiver` were incubated for 21 days with or without indole-3-hutyric acid (IBA) in the medium in darkness or under continuous far-red (8 µmol m-2 s -1, blue, white or red (15 or 36 µmol m-2 s -1) light. `Conference` rooted without IBA when exposed to red, blue or white light while no rooting was observed under far-red light and in darkness. The high rooting efficiency under red and, by contrast, the inhibition under far-red light and darkness suggest the involvement of the phytochrome system in rhizogenesis. The addition of IBA to the culture medium enhanced root production under ah light regimes in both cultivars. Red light, especially at the lower photon fluence rate, had a positive effect by increasing root extension (number x length of roots) and stimulating secondary root forma
Keywords: RHIZOGENES; BIOTECNOLOGIA; CULTIVO IN VITRO; PERA; PYRUS COMMUNIS; ARBOLES FRUTALES; AUXINAS; LUZ; MICROPROPAGACION; Artículos de revista